Principles of GENERAL CHEMISTRY - Silberberg, Martin S. (Martin Stuart), 1945-, author 396354 (Boston, Massachusetts : McGraw-Hill, 2007)
Silberberg's Principles of General Chemistry offers students the same authoritative topic coverage as its parent text, Chemistry: The Molecular Nature of Matter and Change. The Principles text allows for succinct coverage of content with minimal emphasis on pedagogic learning aids. This more streamlined approach to learning appeals to today's efficiency-minded, value-conscious instructors and students without sacrificing depth, clarity, or rigor.